Image Processing Implementation to Classify Coconut Quality Based on Its Color - Musthafa Haris Munandar; Saimarlina Harahap; Feri Irawan (Bulletin of Computer Science and Electrical Engineering, 2022)
At this time the processing of coconut into coconut flour is widely carried out by factories, especially in areas that have a large population of coconuts. Hal ini disebabkan karena keuntungan yang didapat dari hasil pengolahan kelapa tersebut bisa mendapatkan keuntungan yang besar. This is because the profits obtained from the results of processing coconut can get large profits. The problem that has occurred so far is that there are many people who want to process coconuts, but are not accompanied by sufficient knowledge and knowledge of the quality of coconuts that the factory wants, so it is undeniable that there are also many coconuts that have been processed into coconut flour but are not sold in the market. The analysis method used in this study used an image processing method based on digital images with a GUI (Graphical User Interface) interface media that utilizes matlab software. Image processing consists of several processes, the first of which is the operation of changing the color to grayscale. The second process is a grayscale to binary color change operation using the threshold method. The third process is the morphological process of filling holes to remove noise from the threshold image results. The results of the study using the Image Management method are expected to provide knowledge and knowledge to the public about the quality of coconuts expected by the factory, especially to identify the differences between rotten coconuts and rotten coconuts.